Biochemical and Biological Profile of Parotoid Secretion of the Amazonian Rhinella marina (Anura: Bufonidae). (21st February 2019) - Medeiros, Daniel S. S. de; Rego, Tiago B.; Santos, Ana P. de A. dos; Pontes, Adriana S.; Moreira-Dill, Leandro S.; Matos, Najla B.; Zuliani, Juliana P.; Stábeli, Rodrigo G.; Teles, Carolina B. G.; Soares, Andreimar M.; Sperotto, Angelo R. de M.; Moura, Dinara J.; et al.
Abstract : Skin secretions of frogs have a high chemical complexity. They have diverse types of biomolecules, such as proteins, peptides, biogenic amines, and alkaloids. These compounds protect amphibians' skin against growth of bacteria, fungi, and protozoa and participate in defense system against attack from predators. Therewith, this work performed biochemical and biological profile of macroglands parotoid secretion from cane toad. For poison analysis, we performed molecular exclusion and reverse phase chromatography, electrophoresis, and mass spectrometry. Antimicrobial, antiplasmodial, leishmanicidal, cytotoxicity, genotoxicity, and inflammatory activity of crude and/or fractions of R. marina secretion were also evaluated. Fractionation prior to filtration from poison showed separation of low mass content (steroids and alkaloids) and high molecular mass (protein). Material below 10 kDa two steroids, marinobufagin and desacetylcinobufagin, was detected. Crude extract and fractions were active against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Plasmodium falciparum, Leishmania guyanensis, and Leishmania braziliensis . Crude extract was also active against cancer cells although it was not cytotoxic for normal cells. This extract did not show significant DNA damage but it showed an important inflammatory effect in vivo. The information obtained in this work contributes to the understanding of the constituents of R . marina secretion as well as the bioactive potential of these molecules.